Design Of A Detection Device For Dangerous Gas In Electric Cigarette Users Using Arduino Nano - Rizqi, Faris Basyisyar; Kristyawan, Yudi; Santoso, Budi (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2024)
The use of electronic cigarettes (vapes) is expected to be a healthier alternative to tobacco cigarettes. However, various studies have shown that electronic cigarettes also contain hazardous substances such as Benzene and Carbon Monoxide which damage lung health. Previous studies have studied methods for detecting hazardous gases in the lungs, but most of them use expensive devices and complex methods such as SPME–GC/MS which are not easily accessible to the public. This study aims to develop a portable, easy-to-use, and affordable, non-invasive and real-time hazardous gas detection device, especially for Carbon Monoxide and Benzene. This device uses an Arduino microcontroller board and MQ-7 and MQ-135 gas sensors to measure gas levels from users' breath. The results showed that 30 participants exceeded the safe limit of Benzene of 0.5 ppm and 17 participants exceeded the safe limit of Carbon Monoxide of 6 ppm, indicating the potential risk to lung health of electronic cigarette users. These findings can increase public awareness of the dangers of electronic cigarettes and encourage reduction or cessation of their use. Keywords: Gas level detection, Lungs, Electronic cigarettes, Arduino.